Pedagogia, música e autismo: uma análise sobre a literatura pertinente a educação musical e inclusão de pessoas autistas - OLIVEIRA, Edlene Modesto de (2019)
This article presents the results of a bibliographic research which aimed to investigate the relationship between Music Education and Autistic Spectrum Disorder (ASD) published in the portals of ANPED, ANPED NORTE, Capes, SciELO, EDUCERE, Fórum Internacional de Pedagogia (FIPED), Revista Brasileira de Educação (RBE) and Revista Música Hodie, from 2014 to 2018. The bibliographical research (SEVERINO, 2017) resulted in the mapping of 30 texts referring to the subject studied, which were analyzed through qualitative research (LÜDKE; ANDRÉ, 1986 e BOGDAN; BIKLEN, 1999). First we present the results of the mapping, which institutions published on the subject, who were the authors, the methodologies used by them and which areas of knowledge have supported the understanding of the subject. Subsequently, we present a brief overview of what is Autism Spectrum Disorder (ASD), anchored in Brazilian law, the history and characterization of the same. We also discuss the importance of music and the curricular documents that base musical education on the Brazilian scene. Finally, we analyzed the articles found and we discuss how the publications in the area are and what is the importance of music for the development of autistic people. We conclude that the dyad Musical Education and Autism still needs more attention on the part of the academic Community, because there are still few publications in the area, and research needs to increase, in order to provide greater opportunities for musical education to individuals with ASD. However, despite the few researches in the area, it was possible to diagnose, through the publications found, that music in relation to the treatment of autistic people has many benefits, among them stand out, the improvement of the interpersonal relationship and the acquisition of verbal and vocal confidence. For, as we know, the social-affective área and speech are one of the problems that most autistic individuals present.